Facilities of diagnosis and monitoring of optic neuropathy in primary open-angle glaucoma. Part 2 - O. A. Kiseleva; N. V. Balatskaya; A. M. Bessmertny; L. V. Yakubova; V. I. Kotelin (Российский офтальмологический журнал)
The first part of the review was focused on modern methods of instrumental diagnostics of primary open-angle glaucoma [1]. Diagnostic possibilities and informativeness of objective measurable parameters were discussed with regard to special criteria, called clinical endpoints. The second part of the review is dedicated to finding methods of early diagnosis and criteria of the progression of glaucomatous optic neuropathy.